Long-Term Outcomes of Phacoemulsification Surgeries at ECWA Eye Hospital: A Prospective Clinical Cohort Study - Mayor Orezime Atima; Ugbede Idakwo; Oyeronke Komolafe; Eisuke Shimizu; Nakayama Shintaro; Emmanuel Oluwadare Balogun; Emeka John Dingwoke; Ayodele Jacob Orugun; Olalekan Adebayo Ogundare; Pam Douglas Jah (Journal of Ophthalmology)
Background. Phacoemulsification has proven to be a breakthrough technique in cataract surgery. Its popularity has grown dramatically as procedures and equipment have advanced, improving both safety and efficiency. This study presents long-term outcomes from phacoemulsification surgeries performed at the Evangelical Church Winning All (ECWA) Eye Hospital, a tertiary eye care center. Method. This prospective clinical cohort study followed standard practices for operations performed under local anesthesia. Ophthalmologists evaluated long-term outcomes and predictors of improved visual acuity after phacoemulsification cataract surgery. The visual recovery of the patients over time was evaluated, and the factors that influence the gains in vision were identified. Results. A total of 177 patients were subjected to treatment at our facilities during the study period. There were 116 male and 61 female patients, which resulted to a male-to-female ratio of 1 : 0.53. The average age of the patients was 59.18 years with a standard deviation of 11.38 years. Of the 259 eyes treated, 249 eyes (96.1%) achieved a high success rate with visual acuity of 6/6 – 6/18. Ten (10) eyes (3.9%) had moderate acuity between <6/18 and 6/60. Follow-up examinations over five years after phacoemulsification showed poor vision outcomes among old patients. The primary factor that affected improvement in visual acuity among patients was amblyopia, present in 30% of cases. Posterior capsular opacification and macular edema collectively accounted for 20% of poor vision cases, while optic atrophy, glaucoma, and retinal hemorrhage each represented approximately 10% of poor vision cases. Conclusions. The phacoemulsification approach demonstrated a highly effective restoration of vision for the vast majority, while long-term data analysis indicated the potential for age-related variability in postoperative visual gains.